2005
DOI: 10.1002/jcb.20668
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective effect of phloroglucinol on oxidative stress induced cell damage via catalase activation

Abstract: We investigated the cytoprotective effect of phloroglucinol, which was isolated from Ecklonia cava (brown alga), against oxidative stress induced cell damage in Chinese hamster lung fibroblast (V79-4) cells. Phloroglucinol was found to scavenge 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, hydrogen peroxide (H(2)O(2)), hydroxy radical, intracellular reactive oxygen species (ROS), and thus prevented lipid peroxidation. As a result, phloroglucinol reduced H(2)O(2) induced apoptotic cells formation in V79-4 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 46 publications
3
102
0
2
Order By: Relevance
“…Phloroglucinol is a phytochemical derived from edible brown algae with antioxidant, tyrosinase-inhibiting, cytoprotective and anti-inflammatory activities (Kang et al, 2004(Kang et al, , 2006Heo et al, 2005;Yoon et al, 2009;Kim and Kim, 2010). Previously, we demonstrated conducted and the results were compared to the report by Woo and Je (2013 The phloroglucinol content of the chitosan-phloroglucinol conjugate determined using the Folin-Ciocalteau method was 29.28 ± 0.90 mg phloroglucinol/g chitosan-phloroglucinol conjugate.…”
Section: Introductionmentioning
confidence: 96%
“…Phloroglucinol is a phytochemical derived from edible brown algae with antioxidant, tyrosinase-inhibiting, cytoprotective and anti-inflammatory activities (Kang et al, 2004(Kang et al, , 2006Heo et al, 2005;Yoon et al, 2009;Kim and Kim, 2010). Previously, we demonstrated conducted and the results were compared to the report by Woo and Je (2013 The phloroglucinol content of the chitosan-phloroglucinol conjugate determined using the Folin-Ciocalteau method was 29.28 ± 0.90 mg phloroglucinol/g chitosan-phloroglucinol conjugate.…”
Section: Introductionmentioning
confidence: 96%
“…Ecklonia cava, brown algae (Laminariaceae) abundant around Jeju Island in Korea, contains phlorotannin components with known biological activities [6,7]. Phlorotannin has anti-inflammatory effects [6] and protects cells from oxidative stress by scavenging intracellular ROS [7].…”
Section: Introductionmentioning
confidence: 99%
“…Phlorotannin has anti-inflammatory effects [6] and protects cells from oxidative stress by scavenging intracellular ROS [7]. Phlorotannin, which is a phloroglucinol polymer found in marine algal polyphenols, has been identified in various Ecklonia species [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Vendrame and Faria (2011) showed that the addition of 1% of phloroglucinol to the medium increased recovery and survival of Dendrobium nobile protocorms to 68%. Phloroglucinol has antioxidant properties ( Athanasas et al 2004, Benson and Bremner 2004, Kang et al 2006, which may have contributed to the survival of banana cv Grand Naine by reducing oxidative stress in the cells. Rooting of explants was initially observed only in treatment 7 (T7), with average root length of 2.14 cm (Table I).…”
Section: Experiments Imentioning
confidence: 99%